Analisis Faktor – Faktor Yang Mempengaruhi Tingkat Kemiskinan Kabupaten Jember - Fajar Pamungkas; Marseto Marseto; Sishadiyati Sishadiyati (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Poverty is a multidimensional and multisector problem that concerns human dignity. Therefore, poverty alleviation efforts must be implemented in a comprehensive and integrated manner. This research was conducted to find out the influence of Gross Regional Domestic Product (GRDP), regional spending and education on the poverty level of Jember Regency in 2011 to 2020, both partially and simultaneously. The data used by researchers is secondary data obtained from the Jember Regency Central Statistics Agency (BPS) website and the Directorate General of Financial Balance (DJPK) of the Ministry of Finance of the Republic of Indonesia. This quantitative research method uses multiple linear regression analysis with the Ordinary Least Square (OLS) model and is assisted by the SPSS application. The research results show that GRDP and education partially have no effect on the poverty level of Jember Regency, while regional spending has a negative and significant effect on the poverty level of Jember Regency. However, simultaneously, all independent variables have a significant effect on the poverty level of Jember Regency.